Identification of Extended Spectrum Beta Lactamases Producing Pseudomonas aeruginosa from Subclinical Mastitis Milk Samples in an Organized Dairy Farm of SVVU, Andhra Pradesh - Kumari, G. Deepika (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during August 2021 at Buffalo Research Station, Venkatarammanagudem of West Godavari District, Andhra Pradesh, India and was aimed to detect the presence of extended-spectrum beta-lactamases (ESBL) producing P. aeruginosa from sub-clinical mastitis that are apparently healthy Murrah buffaloes. Inflammation of the udder by microbial infection is one of the leading economic disease in the dairy sector. Most of the pathogens especially Pseudomonas aeruginosa are refractory to the antibiotic theraphy. Nowadays, the antimicrobial resistance owed by the bacteria is at an alarming rate. Pseudomonas aeruginosa, a multi drug resistant pathogen carry the extended spectrum beta lactamase genes in its plasmids and thus become resistant to antibiotic therapy. A total of 276 milk samples were collected from 69 milch animals in the month of August, 2021 comprising from all the four quarters of each buffalo. Nine (n=9) (3.26%) P. aeruginosa isolates were identified from the sub-clinical mastitis milk samples from the total 276 samples collected in the study. The isolates on morphological analysis were typical to P. aeruginosa. Seven isolates were positive for phenotypical beta-lactamases production. A total of 1 and 2 isolates were found reactive of the blaSHV and blaOXA genes, and two isolates harboured both blaSHV and blaOXA genes, respectively on PCR assay. No blaTEM gene was found in the isolates. Antibiogram of the ESBL producing P. aeruginosa isolates (n=7) possessed 100% resistance against most of the commonly used antimicrobials like ampicillin, amoxycillin, clindamycin, co-trimoxazole oxytetracycline, streptomycin and ceftriaxone (85%). The P. aeruginosa isolates were sensitive to amikacin (100%), ciprofloxacin (87.4%), gentamicin (84%), norfloxacin (84.8%) and enrofloxacin (82%).